The policy analysis matrix with profit-efficient data: evaluating profitability in rice cultivation - Reig Martinez, E.=700 1 Picazo Tadeo, A.J.; Estruch, V.
(Es, En)
Ilus., 33 ref.
Keywords: POLITICA AGRICOLA COMUN (CE); ANALISIS DE DATOS; RENTABILIDAD; CULTIVO; ARROZ; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH